The concept of social responsibility in the business model of a company - Jevgenijs Kurovs; Tadeusz Waściński (Foundations of Management, 2016)
The article presents a research topic focused on the issues relating to corporate social responsibility (CSR), which is a component of company's business model. The fact that it is a relatively novel trend in the scope of economics inspired us to raise the aforementioned problem of social responsibility in business, since that area of study is still subject to systematization. The existing interpretation of the concept mainly refers to the questions connected with the commercial sector. CSR is said to be an idea, thanks to which enterprises freely take into account the need for social environmental protection and also relations with various groups of stakeholders at the stage of developing their strategy. Therefore, there is a demand for new scientific studies in that scope. Considering the methodological premises of the article, the author carried out an analysis and evaluation of heating companies in Poland and in Latvia between 2002 and 2014. The analysis was conducted in a dynamic perspective with the use of statistical and econometric tools in order to verify the research hypothesis and achieve the purpose of the thesis. It should be highlighted that a survey questionnaire was the main source of the research data. The study covers 212 out of 445 enterprises operating in the heating sector in Poland and 26 out of 45 operating in Latvia.
Keywords: 650; social responsibility; business models; factors: knowledge; macroeconomic; microeconomic; financial; modeling